The Balanced City - Rethinking the Apartment to Provide Families with an Alternative to the Single-Family Home in the Suburbs - Norden, Emma (My University, 2020)
In westernized countries, a single-family home is the housing goal for many people who wish to have children. However, with rising population and increasing urbanization, promoting such a lifestyle is not feasible. On the other hand, some younger families wish to remain in the city because they value the urban lifestyle. Whatever the case, today’s apartments are not designed for familial households and thus, are not often considered to be an appropriate place to raise children. Studies have shown that families desire safe outdoor environments, adequate indoor space, privacy, and ample storage. Not only are apartments becoming more compact, but they also lack efficiency in design. This can be addressed by the concept of adaptibility. Individual rooms must be able to accommodate multi-purpose functions and provide sufficient storage when needed. The placement of the rooms is just as critical. Layouts with several small rooms and an open floor plan limit usability and the possibility for change over the life course. Another concept is that of the private yard. Depending on one’s perspective, the absence of the yard could be viewed as a benefit to multi-dwellings, but the outdoor spaces provided in them are not appropriate substitutes. By integrating supervisable areas that cater to various ages, apartment complexes can maintain a similar idea. Moreover, these spaces can encourage interaction between the residents, helping to foster the emotional and moral support that parenting requires. While the physical attributes are important, the nontangible qualities are factors as well. Neighborhood continuity facilitates a strong sense of community, contributing to a family’s desire to remain in a certain location. Considering the context of Gothenburg, Sweden, this thesis borrows ideas used in co-housing projects and maintains them on a smaller scale. It views the building as the neighborhood, offering various apartment typologies using the same base grid so that families can move within the building. Thus, the result takes the desired qualities of the single-family home and applies them in the context of the apartment.
Keywords: single-family home, apartments, residential housing, urban living, families